Economic Implications of Media Terrorism Reports on Agricultural Productivity and Food Prices in Enugu State - Okoli, Uju Victoria; Obi, Evelyn Chinwe; Chinedu, Richard Ononiwu (Social Science Research, 2022)
Agriculture has remained an important aspect of any economy.However, in Nigeria, incessant clashes between herdsmen and farmers, as well as the activities of the boko haram sect in many states of the federation have posed a serious threat to this key sector in recent years. These groups have had a hand in the death of numerous farmers,non-cultivation of farmlands, burning down of farm produce, and attacks on trucks conveying food to different parts of the country, with the consequent reduction in the quantity of food production and then the hike in food prices in Nigeria.Of course, the media, as expected, has been at the forefront of reporting these attacks on farmers. Anchored on the Agenda Setting Theory, this study explores farmers’ responses to theinfluence of these media reports on agricultural productivity as well as food prices. Data were drawn from 390 farmers in Enugustate using simple random sampling technique and chi-square (x2) was used to test the stated hypotheses.Findings showed that the farmer’s exposure to media terrorism reports was high, and that the respondents agreed that media terrorism reports have a significant negative impact on agricultural productivity and food prices. The study therefore recommends that the government and other relevant agencies should ensure that the media ecosystem is also filled with alternative content that focuses on informing and educating the farmers on the best agricultural practices rather than mostly on terror reports.